UTILIZATION OF ARABICA COFFEE HUSK FROM THE PULPING PROCESS FOR BIOETHANOL PRODUCTION - Raudah, R; Ernawati, E (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACTOne of the sugar sources that can be used as a raw material for bioethanol production is the waste from Arabica coffee husk. This waste is chosen as the base material for bioethanol production due to its high reducing sugar content, its non-competition for food resources, and its abundant availability. The research employs the yeast Saccharomyces cerevisiae using fermentation methods to investigate the effects of fermentation time and yeast dosage on achieving optimal bioethanol concentration. This study varied the fermentation times at 62, 72, and 82 hours, as well as the addition of yeast at 0.5 g, 1 g, and 1.5 g. The resulting fermentation liquid was then distilled, and the bioethanol concentration was tested using a refractometer. Subsequently, the bioethanol concentration was analyzed using gas chromatography. The results showed that at a fermentation time of 72 hours with 1.5 g of yeast, bioethanol production reached 62%, with a concentration of 97.72% (%v/v).Keywords: bioetanol, fermentasi, kopi, Saccharomyces cerevisiae, khromatografi gas.